Relationship Between Dairy Cattle Farming Motivation and Farmer’s Attitude Towards Portable Milking Machine - Fransiskus Trisakti Haryadi; Adiarto Adiarto; Asmaul Fauzi Latif Fatkhur Rohman (Buletin Peternakan, 2019)
The research was a case study for dairy cattle farmers being the members of Sarono Makmur Cooperative at Cangkringan District, Sleman Regency, Yogyakarta. The objectives of the research were (1) to explore dairy cattle farming motivation based on multidimensional approach, and (2) to analyze the relationship between the dimensions of dairy cattle farming motivation and the attitude of farmers towards the using of portable milking machine. 63 dairy cattle farmers, selected by purposive random sampling, participated in the research. Data were collected using survey method by interviewing the farmers based on the questionnaire already prepared. Spearman correlation was used to analyze the data. The results showed that most of farmers had high dairy cattle farming motivation including ease of farming management (95.24%), family labor utilization (93.65%), economic motives(92.06%),safety motives (92.06%), and land utilization (84.13%). As well as the attitudes, most of farmers (92.06%) had positive attitudes towards portable milking machine utilization. There were positive significant relationship between attitude and family labor utilization (P<0.05), safety in farming (P<0.05), economic motives (P<0.10), and land utilization (P<0.10). The conclusion of the research was that the high motives of family labor utilization, safety, economic, and land utilization to encourage the farmers raising dairy cattle, the high positive attitude of farmers towards the utilization of portable milking machine.